Analysis of cesarean section delivery at Nova Bila Hospital according to the Robson Classification - Bilobrk Josipović, Ljiljana; Dizdarević Stojanković, Jadranka; Brković, Irma (2015)
An increase in Cesarean section birth rate is evident worldwide, especially in developed and developing countries. Since this trend is rapidly gaining epidemic status with unpredictable consequences regarding the reproductive and overall women's health, there is a need for systematic collection and analysis of Cesarean section occurrence data. At this moment, there is no standardized, internationally accepted classification that would be easy to understand and simple to apply. In 2001, Robson Cesarean section classification in ten groups, which might satisfy good classification criteria, was published. In this paper, we have retrospectively collected and sorted the data on Cesarean section births from the "Dr Fra Mato Nikolić" Croatian hospital in Nova Bila, according to Robson classification, for the period from January 1st, 1998 to December 31st, 2007. During this period, 6603 women have given birth. Of these, 1010 opted for Cesarean section (15.30%). The largest group of women giving birth belongs to group 3 (multiparous, single pregnancy, head down, 37 weeks gestation age or more, spontaneous labor), where 49.74% of all the analyzed births belong. The largest group for those with Cesarean sections is group 5 (previous Cesarean section) with 26, 93% of all the Cesarean sections. Our results are similar to the results of studies done elsewhere in the world. Robson classification identifies the risk groups with high Cesarean section percentage and is appropriate for long-term tracking and international comparison of the recognized increase of the Cesarean section trend.
Projekt MZOS
ENG